2006
DOI: 10.1007/s10549-006-9335-4
|View full text |Cite
|
Sign up to set email alerts
|

MMP-2 and MMP-9 activity is regulated by estradiol and tamoxifen in cultured human breast cancer cells

Abstract: Sex steroids play a dominant role in breast carcinogenesis by still largely unknown mechanisms. Matrix metalloproteinases (MMPs) have been extensively studied in the context of matrix biology but it is not known if sex steroids affect MMPs in breast cancer. MMPs degrade extracellular matrix components enabling tumor cell invasion and metastasis, but may also regulate the bioavailability of a variety of biologically active molecules such as anti-angiogenic fragments, which may be beneficial for the host. This s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

9
71
1
1

Year Published

2008
2008
2021
2021

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 84 publications
(82 citation statements)
references
References 42 publications
9
71
1
1
Order By: Relevance
“…Garvin et al (2006) also demonstrated that similar events also occurred in ex vivo cultured normal human breast tissue (Garvin et al, 2006). In addition, MMP-9 are closely associated with tumor growth, invasion and metastasis (Versteeg et al, 2008) and estrogen has been shown to regulate the activity of MMP-2 and MMP-9 in breast cancer cells (Nilsson et al, 2007).…”
Section: Discussionmentioning
confidence: 81%
“…Garvin et al (2006) also demonstrated that similar events also occurred in ex vivo cultured normal human breast tissue (Garvin et al, 2006). In addition, MMP-9 are closely associated with tumor growth, invasion and metastasis (Versteeg et al, 2008) and estrogen has been shown to regulate the activity of MMP-2 and MMP-9 in breast cancer cells (Nilsson et al, 2007).…”
Section: Discussionmentioning
confidence: 81%
“…2B) 2D). It should be stated that the fluorogenic substrate used in the activity assay may also be cleaved by MMP-2; however, as we have showed previously, the induced levels of active MMP-2 in MCF-7 cells are considerably lower than the levels of active MMP-9 [26].…”
Section: Inhibiting Extracellular Mmp Activity Restored the Tamoxifenmentioning
confidence: 59%
“…In this regard, we have previously shown tamoxifen may also alter the extracellular levels of natural inhibitors of MMPs [26]. Therefore, we verified if the altered MMP-9 protein levels also affected the extracellular physiological MMP activity using a substrate activity assay.…”
Section: Inhibiting Extracellular Mmp Activity Restored the Tamoxifenmentioning
confidence: 71%
See 2 more Smart Citations